Improving patient safety through the involvement of patients: development and evaluation of novel interventions to engage patients in preventing patient safety incidents and protecting them against unintended harm - John Wright; Rebecca Lawton; Jane O'Hara; Gerry Armitage; Laura Sheard; Claire Marsh; Angela Grange; Rosemary RC McEachan; Kim Cocks; Susan Hrisos; Richard Thomson; Vikram Jha; et al. (NIHR Journals Library, 2016)
Background: Estimates suggest that, in NHS hospitals, incidents causing harm to patients occur in 10% of admissions, with costs to the NHS of > £2B. About one-third of harmful events are believed to be preventable. Strategies to reduce patient safety incidents (PSIs) have mostly focused on changing systems of care and professional behaviour, with the role that patients can play in enhancing the safety of care being relatively unexplored. However, although the role and effectiveness of patient involvement in safety initiatives is unclear, previous work has identified a general willingness among patients to contribute to initiatives to improve health-care safety. Aim: Our aim in this programme was to design, develop and evaluate four innovative approaches to engage patients in preventing PSIs: assessing risk, reporting incidents, direct engagement in preventing harm and education and training. Methods and results: We developed tools to report PSIs [patient incident reporting tool (PIRT)] and provide feedback on factors that might contribute to PSIs in the future [Patient Measure of Safety (PMOS)]. These were combined into a single instrument and evaluated in the Patient Reporting and Action for a Safe Environment (PRASE) intervention using a randomised design. Although take-up of the intervention by, and retention of, participating hospital wards was 100% and patient participation was high at 86%, compliance with the intervention, particularly the implementation of action plans, was poor. We found no significant effect of the intervention on outcomes at 6 or 12 months. The ThinkSAFE project involved the development and evaluation of an intervention to support patients to directly engage with health-care staff to enhance their safety through strategies such as checking their care and speaking up to staff if they had any concerns. The piloting of ThinkSAFE showed that the approach is feasible and acceptable to users and may have the potential to improve patient safety. We also developed a patient safety training programme for junior doctors based on patients who had experienced PSIs recounting their own stories. This approach was compared with traditional methods of patient safety teaching in a randomised controlled trial. The study showed that delivering patient safety training based on patient narratives is feasible and had an effect on emotional engagement and learning about communication. However, there was no effect on changing general attitudes to safety compared with the control. Conclusion: This research programme has developed a number of novel interventions to engage patients in preventing PSIs and protecting them against unintended harm. In our evaluations of these interventions we have been unable to demonstrate any improvement in patient safety although this conclusion comes with a number of caveats, mainly about the difficulty of measuring patient safety outcomes. Reflecting this difficulty, one of our recommendations for future research is to develop reliable and valid measures to help efficiently evaluate safety improvement interventions. The programme found patients to be willing to codesign, coproduce and participate in initiatives to prevent PSIs and the approaches used were feasible and acceptable. These factors together with recent calls to strengthen the patient voice in health care could suggest that the tools and interventions from this programme would benefit from further development and evaluation. Trial registration: Current Controlled Trials ISRCTN07689702. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.